PENGARUH KINERJA KOMITE AUDIT TERHADAP TERJADINYA KESULITAN KEUANGAN - Sari Rahmadhani (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
This study examines financial difficulties can occur if the auditcommittee does not perform its roles and responsibilities effectively. Theperformance of an audit committee can be measured by its characteristics,including the size, independence, activity of the audit committee, and thecompetencies of audit committee members. Based on the discussion of researchresults described above, then there are some implications found and can addinformation for the company, investors and other parties associated with thecompany's activities. The results conclude that the size of the auditcommittee, the independence of the audit committee and the financialknowledge of audit committee members can not prove a significant influenceon financial difficulties. This research proves that the existence of women ingender audit committee is able to avoid the company from financialdifficulties. The frequency of meetings of audit committee members can proveto have a significant negative effect on the financial difficulty. This isbecause the frequency of meetings of members of the audit committee has arole in changing the pattern of management behavior and communicationamong members more structured so that the company's condition will notexperience financial difficulties.